Hubungan Pengetahuan Dengan Sikap Dalam Mengatasi Dismenore Pada Mahasiswi Prodi S1 Gizi Fakultas Ilmu Kesehatan Universitas ‘Aisyiyah Yogyakarta - Deva Indowidy Santiya; Nurul Mahmudah; Intan Mutiara Putri (Poltekkes Kemenkes Padang, 2022)
Dysmenorrhea is one of the disorders during menstruation. Dysmenorrhea affects quality of life by limiting physical activity, and impairing focus. The study aims to determine the correlation between knowledge and attitude in overcoming dysmenorrhea in students of Nutrition Study Program, Faculty of Health Sciences, Universitas 'Aisyiyah Yogyakarta. This study employed an analytic observational with cross sectional approach. The population in this study were students of the 6th semester of Nutrition Study Program by using a total sampling technique, a sample of 65 respondents was obtained. The data was collected using an instrument in the form of a knowledge and attitude questionnaire in overcoming dysmenorrhea. The data analysis used the Chi Square statistical test. The results of the study showed that there were sufficient knowledge about dysmenorrhea as many as 30 people (46.2%) and negative attitudes in overcoming dysmenorrhea as many as 39 people (60.0%). The results of the Chi Square statistical test obtained a significance value of 0.000 so that (p < 0.05) means that there was a significant correlation between knowledge and attitudes in overcoming dysmenorrhea. It is known that the correlation coefficient is 0.620, which means that the category of the closeness of the correlation is strong. In conclusion, there is a significant correlation between knowledge and attitudes in overcoming dysmenorrhea. The respondents are suggested to increase knowledge about dysmenorrhea, so that they can overcome dysmenorrhea appropriately.